Nutrients, bioactive compounds, and minerals in the juices of 16 varieties of apple (Malus domestica) harvested in Austria: A four-year study investigating putative correlations with weather conditions during ripening. (15th February 2021) - Tschida, Aurelia; Stadlbauer, Verena; Schwarzinger, Bettina; Maier, Martin; Pitsch, Johannes; Stübl, Flora; Müller, Ulrike; Lanzerstorfer, Peter; Himmelsbach, Markus; Wruss, Jürgen; Klanert, Gerald; Schurr, Jonas; et al.
Graphical abstract: Highlights: Large-scale study including 4 harvest years and up to 72 apple varieties. Correlations between weather parameters and apple juice nutrients, minerals and bioactives. Results suggest weak to moderate correlations between apple juice composition and weather conditions. Strongest correlations were found between ripeness and weather parameters. Abstract: This study was conducted to examine putative correlations between weather parameters during April-September and the amounts of nutrients, minerals and bioactive compounds in the juices of 16 apple varieties from four harvest years in Lower Austria. For most sugar-parameters, negative correlations were found with the total precipitation ( r between −0.42 and −0.64). Conversely, positive correlations were observed with the mean air temperature ( r between 0.32 and 0.66), the global radiation ( r between 0.32 and 0.61) and the number of tropical days ( r between 0.39 and 0.51). The sum of 14 polyphenols (HPLC quantitation) was positively correlated with the mean air temperature and global radiation (rs 0.44 and 0.42). Negative correlations were observed between the global radiation and potassium, magnesium and calcium contents (correlation coefficients −0.49, −0.68 and −0.69). We conclude that increased temperatures and global radiation can be correlated with enhanced sugar synthesis and polyphenol formation.